The cGas–Sting Signaling Pathway Is Required for the Innate Immune Response Against Ectromelia Virus - Cheng, Wen-Yu; He, Xiao-Bing; Jia, Huai-Jie; Chen, Guo-Hua; Jin, Qi-Wang; Long, Zhao-Lin; Jing, Zhi-Zhong (Frontiers in Immunology, 2018)
Activation of the DNA-dependent innate immune pathway plays a pivotal role in the host defense against poxvirus. Cyclic GMP-AMP synthase (cGAS) is a key cytosolic DNA sensor that produces the cyclic dinucleotide cGMP-AMP (cGAMP) upon activation, which triggers stimulator of interferon genes (STING), leading to type I Interferons (IFNs) production and an antiviral response. Ectromelia virus (ECTV) has emerged as a valuable model for investigating the host–Orthopoxvirus relationship. However, the role of cGas–Sting pathway in response to ECTV is not clearly understood. Here, we showed that murine cells (L929 and RAW264.7) mount type I IFN responses to ECTV that are dependent upon cGas, Sting, TANK binding kinase 1 (Tbk1), and interferon regulatory factor 3 (Irf3) signaling. Disruption of cGas or Sting expression in mouse macrophages blocked the type I IFN production and facilitated ECTV replication. Consistently, mice deficient in cGas or Sting exhibited lower type I IFN levels and higher viral loads, and are more susceptible to mousepox. Collectively, our study indicates that the cGas–Sting pathway is critical for sensing of ECTV infection, inducing the type I IFN production, and controlling ECTV replication.